We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
110
1
avatar+125 

what is (f-g)(x) ?

 

f(x)=x4 -3x2 +5x-7

g(x)=x3 -3x2 +3x-2

 

enter your answer is standard form

(f-g) (x) =?

 Apr 4, 2019

Best Answer 

 #1
avatar+18754 
+3

=   x^4 - 3x^2 + 5x - 7       -    (x^3 - 3x^2 + 3x - 2)

= x ^4 - 3x^2 + 5x - 7        - x^3 + 3x^2 - 3x + 2     = .......... ?     YOU should be able to take it from here !   

 Apr 4, 2019
 #1
avatar+18754 
+3
Best Answer

=   x^4 - 3x^2 + 5x - 7       -    (x^3 - 3x^2 + 3x - 2)

= x ^4 - 3x^2 + 5x - 7        - x^3 + 3x^2 - 3x + 2     = .......... ?     YOU should be able to take it from here !   

ElectricPavlov Apr 4, 2019

21 Online Users